Poisoning Crimes and Forensic Toxicology Since the 18th Century - Watson, Katherine D. (Acad Forensic Pathol, 2020)
The easy availability of deadly poisons in 19th-century Britain, Western Europe, and the United States led to widespread public anxiety about the prevalence of murder by poison, resulting in what might be termed a “poison panic.” The fear was fed by well-publicized reports of trials and executions which, though not especially numerous, seemed indicative of the dangerous incidence of a unique type of homicide, one that was particularly difficult to prevent or detect. As a result, poisoning crimes stimulated the development of the earliest medicolegal specialism, forensic toxicology, and consequently the careers of some of the best known expert witnesses of the Victorian era, including Mathieu Orfila, Alfred Swaine Taylor, Thomas Stevenson, and Theodore Wormley. This article traces the history of poisoning crimes and the related medico-scientific discipline of forensic toxicology using textbooks, key trials, and crime statistics to examine and evaluate their contribution to the historical development of forensic expertise and practice.